Phylogenetic mapping of scale nanostructure diversity in snakes - Arrigo, Marcelle I. (BMC Evol Biol, 2019)
BACKGROUND: Many species of snakes exhibit epidermal surface nanostructures that form complex motifs conferring self-cleaning properties, and sometimes structural iridescence, to their skin. RESULTS: Using confocal microscopy, we show that these specialised cells can be greatly elongated along their left-right axis and that different types of nanostructures are generated by cell borders and cell surface. To characterise the complexity and diversity of these surface gratings, we analysed scanning electron microscopy images of skin sheds from 353 species spanning 19 of the 26 families of snakes and characterised the observed nanostructures with four characters. The full character matrix, as well as one representative SEM image of each of the corresponding species, is available as a MySQL relational database at https://snake-nanogratings.lanevol.org. We then performed continuous-time Markov phylogenetic mapping on the snake phylogeny, providing an evolutionary dynamical estimate for the different types of nanostructures. These analyses suggest that the presence of cell border digitations is the ancestral state for snake skin nanostructures which was subsequently and independently lost in multiple lineages. Our analyses also indicate that cell shape and cell border shape are co-dependent characters whereas we did not find correlation between a simple life habit classification and any specific nanomorphological character. CONCLUSIONS: These results, compatible with the fact that multiple types of nanostructures can generate hydrophobicity, suggest that the diversity and complexity of snake skin surface nano-morphology are dominated by phylogenetic rather than habitat-specific functional constraints. The present descriptive study opens the perspective of investigating the cellular self-organisational cytoskeletal processes controlling the patterning of different skin surface nanostructures in snakes and lizards. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12862-019-1411-6) contains supplementary material, which is available to authorized users.